PEMANFAATAN BUKU KIA BERHUBUNGAN DENGAN KEMAMPUAN MENGENALI TANDA BAHAYA NIFAS PADA IBU NIFAS DI WILAYAH KERJA PUSKESMAS KLATAK KABUPATEN BANYUWANGI - Rofika, Lutvia Dwi; Wardani, Endah Kusuma; Rachman, Machria (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
I One major factor contributing to Indonesia's persistently high maternal death rate is infection, which typically happens in the postpartum phase. From the placenta's birth to 42 days after giving birth, there is a postpartum phase. One way to describe the postpartum period is as a transitional phase during which the reproductive organs revert to their pre-pregnancy state. A lot can happen during this period, so it’s important for postpartum mothers to stay aware of any changes in their bodies. By recognizing early signs, they can address potential issues quickly or even prevent them altogether. The utilization of KIA books can serve as a valuable resource for learning about postpartum issues; yet, many postpartum moms continue to use them in suboptimal ways. This study's objective is to In the Klatak Health Center's working area in Banyuwangi Regency, the usage of KIA books is associated with the ability to identify postpartum moms' danger signs. A one-shot, pre-experimental case study approach was used in this study. The sample, consisting of 30 respondents, was selected through purposive sampling. Analysis of the study results using the t-test revealed a p-value of 0.0000 < 0.05, indicating that the use of KIA books had a significant independent effect on the implementation of screening and complication detection for postpartum women. These findings demonstrate how crucial it is for new mothers to use the KIA book. Mothers will find it simpler to comprehend all of the challenging circumstances that could arise throughout the postpartum phase.Keywords: danger sign postpartum, KIA book, screening